Listening Section of the Simulated Toefl Test: Semantic and Pragmatic Context Analysis - Mustafa Hasan Ahtif; Nilotpala Gandhi (Journal of Education Review Provision, 2022)
Language users are impacted by sociolinguistic factors like semantics and pragmatics in every circumstance. Even in a proficiency test, those two contexts are present because they serve as the test's framework. In order to identify the semantic and pragmatic settings in the TOEFL test simulation for the Listening component, research was done. In this study, the researcher used a qualitative descriptive strategy, using document analysis as the instrument. The study's focus was the FORUM TENTOR INDONESIA publication TOP NO.  1TOEFL SIMULATION. The outcome demonstrates that different kinds of semantic and pragmatic context were present in the test simulation. In 8 of the 30 questions that were analyzed, there were semantic contexts. Semantic contexts of three different types—meaning, semantic feature, and semantic roles—were discovered. Semantic Roles (4 Questions), Semantic Feature (2 Questions), and Meaning are the other predominant semantic types (2 Questions). The Pragmatic context quantities, however, are more prevalent than the Semantic context. Because one test item can contain multiple types of pragmatic language, 40 questions from the 30 studied items were found to have pragmatic contexts. Additionally, the majority of the pragmatic inquiries were of the Reference type since the narrator of the listening section used referring to formulate the question. Context, Politeness, Reference, and Speech Act are the different types of pragmatic context that can be encountered. Reference-type pragmatic contexts are the most common (25 questions).